Copyright of Afghanistan Recent Infringements and Developments - Sabghatullah Ghorzang (LSPR Institute of Communication & Business, 2026)
This article looks at the complicated landscape of copyright law in Afghanistan, examining its historical development, current legal framework and current challenges. Focusing on recent infringements and developments, the study uses a mixed methods approach and involves 22 participants, including experienced writers and representatives of prominent publishing houses. The research questions guide the investigation, which aims to uncover notable developments and infringements, understand their impact on international copyright law and provide insights for improvement. The comprehensive literature review contextualizes the challenges and draws on global perspectives to illustrate the pervasive nature of copyright issues. The study examines Afghanistan's 2008 Copyright Law, which covers various creative works and emphasizes alignment with international treaties. The research methodology includes a carefully crafted questionnaire that addresses awareness, recent changes in the law, and strategies for improvement. Analysis of the participant data reveals a nuanced landscape, showing diverse insights from accomplished writers and influential publishing owners. The study identifies key themes, such as concerns about the implementation gap in existing copyright laws, the impact of socio-political conditions on infringement, and the need for greater public awareness. Comparisons between writers and publishers reveal nuanced emphases, with writers emphasizing the personal impact of plagiarism and publishers focusing on economic issues. In conclusion, the study highlights the complex challenges Afghanistan faces in enforcing copyright. The participants argue for stronger legal sanctions, more resources and education.